TRANSFORMING ENGLISH AS A SECOND LANGUAGE EDUCATION IN UZBEKISTAN: THE MOTIVATIONAL IMPACT OF AI AND VIRTUAL REALITY - Nasirova Umida Kamolovna (Bright Mind Publishing, 2025)
This article explores the motivational impact of artificial intelligence (AI) and virtual reality (VR) technologies on English as a Second Language (ESL) education in Uzbekistan. With the rapid digital transformation of education, AI-powered assistants and immersive 3D virtual environments have emerged as innovative tools that support interactive learning, instant feedback, and gamified engagement. Drawing on global and local perspectives, the study highlights how AI applications—such as intelligent tutoring systems, chatbots, and gamification platforms—personalize the learning process, foster autonomy, and sustain learner motivation. Similarly, VR technologies create immersive and authentic contexts for language practice, enabling learners to engage in real-life simulations and cross-cultural interactions that go beyond the limitations of traditional classrooms. The paper also examines challenges related to infrastructure, teacher readiness, and access to digital resources, particularly in rural areas of Uzbekistan. Findings suggest that the integration of AI and VR can significantly enhance motivation, learner-centered practices, and overall effectiveness of ESL education, provided that implementation strategies address accessibility and pedagogical support.
Keywords: Artificial Intelligence (AI), Virtual Reality (VR), English as a Second Language (ESL), Language Learning Technologies, Gamification, Digital Education.